KEBIJAKAN HEDGING DENGAN DERIVATIF VALUTA ASING PADA PERUSAHAAN PUBLIK DI INDONESIA - Ekayana Sangkasari Paranita (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
The purpose of this paper is investigates the corporate hedging policy among Indonesiancapital market to provide empirical evidence on the determinants of the hedging policy.The research using a sample of 150 non-financial manufacturing firms over the period2010. The methodology taken is application of logit regression framework and paneldata technique. It is found that a few Indonesia firms hedge market risks. There is asignificant positive correlation between financial distress costs, underinvestment costs,and assets substitution costs towards corporate hedging policy. Hence, it seems thatIndonesian firms do not assign hedging to respond to tax benefit. At present, most of theIndonesian firms are either cautions or unsure about the use of derivative instruments.There is a need to inform managers about usefulness of the derivatives and market riskreporting that would contribute to greater financial transparency. The findings imply thatfirms should disclose in their publicy financial report that they truly use derivatives forhedging purposes. This paper adds contribution to risk management research byproviding strong empirical evidence of corporate hedging policy in Indonesia as one ofthe emerging market countries.